Edukasi Budi Daya Ikan Lele Kolam Terpal di Panti Asuhan Nurul Ikhsan Merawang Kabupaten Bangka - Fika Dewi Pratiwi; Eddy Jajang Jaya Atmadja; Rufti Puji Astuti (Institut Pertanian Bogor, 2020)
Growing catfish is relative needs a short time (3-4 months) that can be profitable for cultivators. The increase of public demand for catfish provides an opportunity for everyone to carry out this business, including the orphanage students. Because of this, the orphan empowerment aimed to educate and practice the basics of conventional catfish farming used probio-Fm technology. The program was conducted in November-December 2018. The empowerment program location was at Nurul Ikhsan Orphanage, Batu Rusa village, Merawang District, Bangka Regency, Bangka Belitung Islands Province. The participants were 40 orphans. Four steps of the program consisted of 1) preparation (coordination, survey, and materials preparation), 2) discussion of the training materials (management of conventional catfish farming) 3) Field practice (demonstration of plastic fish tank design and application of probio-Fm) 4) Monitoring and evaluation (the distribution of the questionnaire). Based on the questionnaire, the average of participants (50 %) agreed if they categorized as motivated participants in the program, the Transfering theory and practice methods were easy to understand and follow their needs. Besides, they agreed on the continuity of the program. We concluded that the program succeeded in educating the orphan student about cultivating the catfish with the conventional method based on probio-Fm, however, catfish maintenance should be accompanied by the intensive assistance until harvest. Educating catfish business analysis could more motivate the orphanage student to practice catfish farming.